Empowering Gaza through solar energy: A scalable humanitarian framework for electricity and water security - La Scala, Massimo (Plurimondi, 2025)
This paper presents a framework for providing rapid humanitarian relief of Gaza's critical electricity and water crises through solar energy deployment. With a population density exceeding 6,000 inhabitants per km² and approximately 90% of electricity infrastructure damaged post-2023, Gaza faces severe shortages affecting 2.2 million people. The study demonstrates that Gaza's abundant solar irradiation offers a viable solution through scalable photovoltaic microgrids. A phased implementation strategy is proposed, beginning with mobile emergency systems and progressing to community-scale microgrids serving approximately 100 households each. These systems integrate solar generation (70-80 kWp per microgrid), battery storage, and solar-powered desalination to address both electricity and water needs simultaneously. The framework employs demand-side management through "electric springs" technology, using water desalination as a flexible load to optimize battery utilization. Preliminary estimates indicate that basic electricity and water needs could be met for a pre-war population through a feasible investment. This decentralized approach offers enhanced resilience, local maintenance capacity, and potential integration with future centralized infrastructure, while providing immediate humanitarian relief. The modular nature of available microgrid technology makes it highly scalable, enabling the development of urban environments with elevated living standards once the emergency has passed. This article is based on the author’s presentation “Empowering Gaza: A Humanitarian Appeal for Power and Water Through a Scalable Solar Energy Vision” (Workshop “Framework Gaza Phoenix” organized by Politecnico di Bari, Bari, 16 July 2025).  The rapid and severe evolution of the crisis in the area may have changed some data reported here as presented at the date of the meeting.